2012
DOI: 10.12697/poa.2011.20.28
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of human B-defensin 2, TNF-alpha, IL-1 alpha, IL-6 and IL-8 in psoriatic skin

Abstract: Psoriasis is a chronic, inflammatory, proliferative condition of the skin, clinically characterized by red, scaly plaques. Psoriasis has a large and heterogenous genetic and immunologic background with the dysregulation of the host defense system. The human keratinocytes obtained from psoriasis lesions are a very rich source to various antimicrobial peptides. Both Th 17 and Th 1 pathways play a role in the pathogenesis of psoriasis. Our aim of the study was to evaluate the expression of human beta defensin 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In addition, the results of our study are in concordance with a study which evaluated the expression of human beta-defensin 2, TNF alpha and interleukins 1 alpha, 6 and 8 in 14 skin biopsies of psoriatic lesions by immunohistochemical staining. A statistically significant correlation between human beta-defensin 2 and IL-6 was found in the skin biopsies [48]. Another study indicated that hBD2 is related to cytokine production.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the results of our study are in concordance with a study which evaluated the expression of human beta-defensin 2, TNF alpha and interleukins 1 alpha, 6 and 8 in 14 skin biopsies of psoriatic lesions by immunohistochemical staining. A statistically significant correlation between human beta-defensin 2 and IL-6 was found in the skin biopsies [48]. Another study indicated that hBD2 is related to cytokine production.…”
Section: Discussionmentioning
confidence: 91%